2019
DOI: 10.1007/s13213-019-1440-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of exopolysaccharide production by probiotic yeast Lipomyces starkeyi VIT-MN03 using response surface methodology and its applications

Abstract: In the present study, the cultural conditions for exopolysaccharide (EPS) production from probiotic yeast Lipomyces starkeyi VIT-MN03 were optimized using response surface methodology (RSM) to maximize the yield of EPS. Interactions among the various factors viz. sucrose concentration (1-3 g%), NaCl concentration (2-4 g%), pH (3-5), temperature (20-30°C), and incubation period (20-40 days) during EPS production were studied using Box-Behnken design (BBD). The EPS was purified and characterized using various in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 57 publications
0
13
1
1
Order By: Relevance
“…Thirumal et al [7] demonstrated that the exopolysaccharide produced by L. starkeyi may contain mannose and galactose. Compared with the study of Mangala et al [17], it could be found that although exopolysaccharides were both yielded by L. starkeyi, their monosaccharide compositions were different. These differences were probably caused by genetic differences between different strains, and the different compositions of monosaccharides will lead to different structural and functional properties.…”
Section: Monosaccharide Compositioncontrasting
confidence: 83%
“…Thirumal et al [7] demonstrated that the exopolysaccharide produced by L. starkeyi may contain mannose and galactose. Compared with the study of Mangala et al [17], it could be found that although exopolysaccharides were both yielded by L. starkeyi, their monosaccharide compositions were different. These differences were probably caused by genetic differences between different strains, and the different compositions of monosaccharides will lead to different structural and functional properties.…”
Section: Monosaccharide Compositioncontrasting
confidence: 83%
“…Additionally, it also helps in the treatment for irritable bowel syndrome (IBS), gastrointestinal dysbiosis, as for other intestinal disorders [2][3][4]. Most of the known probiotics are Generally Recognized As Safe (GRAS), including Lactobacillus and Bifidobacterium species, and certain yeast strains such as Saccharomyces boulardii, S. cerevisiae CNCM I-3856, and Lipomyces starkeyi VIT-MN03 [3][4][5][6]. Several mechanisms are proposed on how these microorganisms are beneficial to the host wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Meyerozyma caribacca 9C and 9D yeast strains expressed favorable properties of probiotics with 99.36% and 98.52% of auto aggregation respectively after 24 h of incubation time and these outcomes are near or higher than the reference strain [34] . Lipomyces starkeyi VIT-MNO3 revealed good probiotic assets with 95% of self-adhesion [35] . The auto aggregation capacity of Candida quercitresa CCMA 0560 isolated from indigenous fermented foods exhibited 95%±3.6% which was similar to reference strain Saccharomyces boulardii with 95.5%±0.1%.…”
Section: Probiotic Attributes Of Yeastsmentioning
confidence: 99%
“…The cell surfaces of yeast with high hydrophobicity afford both the greater aggregation capacity and also the adhesion capacity Debaryomyces hansenii in the cell surface hydrophobicity assay with 92.23±1.2% of hydrophobicity showed noticeable results when compared to control strain [24] . Lipomyces starkeyi VIT-MNO3 revealed good probiotic assets with 85% hydrophobicity [35] . About 68.53%±11.37% of cell surface hydrophobicity was reported by Kazachstenia turicansis whereas percentage of Saccharomyces cerevesiae JYC2619 was 6.10±1.5% [33] .…”
Section: Probiotic Attributes Of Yeastsmentioning
confidence: 99%